Migraine with aura attacks overriding dreams - Kowacs, Pedro André (2011)
While the anatomical pathways involved in migraine with aura are near to be completely known, those involved in dreaming remain less studied. We aimed to describe two cases of migraine with visual aura, whose migraine auras would override their dreams, and to discuss the pathways involved in visual aura and in dreams. The following hypothesis can derive from the above mentioned cases: a) visual aura projects over hippocampal and parahippocampal image templates where they fuse in an unique image; b) memory banks use the extrastriatal occipital cortex to form they image templates, fusion with visual aura occurring during this process; c) both process occur independently, but fuse within visual association areas. The description of case reports like the two above is important to understand the aura phenomenon and the dreaming process and to reinforce the cortical role for these manifestations.